Cytotoxic effect of sanguiin H-6 on MCF-7 and MDA-MB-231 human breast carcinoma cells. Issue 18 (15th September 2017) - Park, Eun-Ji; Lee, Dahae; Baek, Seon-Eun; Kim, Ki Hyun; Kang, Ki Sung; Jang, Tae Su; Lee, Hye Lim; Song, Ji Hoon; Yoo, Jeong-Eun
Graphical abstract: Abstract: Sanguiin H-6 is a dimer of casuarictin linked by a bond between the gallic acid residue and one of the hexahydroxydiphenic acid units. It is an effective compound extracted from Rubus coreanus . It has an anticancer effect against several human cancer cells; however, its effect on breast cancer cells has not been clearly demonstrated. Thus, we aimed to investigate the anticancer effect and mechanism of action of sanguiin H-6 against two human breast carcinoma cell lines (MCF-7 and MDA-MB-231). We found that sanguiin H-6 significantly reduced cell viability in a concentration-dependent manner. It also increased the rates at which MCF-7 and MDA-MB-231 cells underwent apoptosis. Furthermore, sanguiin H-6 induced the cleavage of caspase-8, caspase-3, and poly(ADP-ribose) polymerase, which resulted in apoptosis. However, cleavage of caspase-9 was only detectable in MCF-7 cells. In addition, sanguiin H-6 increased the ratio of Bax to Bcl-2 in both MCF-7 and MDA-MB-231 cells. These findings suggest that sanguiin H-6 is a potent therapeutic agent against breast cancer cells. In addition, it exerts its anticancer effect in an estrogen-receptor-independent manner.